Impact of Social Factors on Generation Z’s Buying Decision Process of Organic Facial Care Products in Thailand - Changchenkit Chuenjit; Sutthachai Chongrak (SHS Web of Conferences)
The objectives of this research were to study Generation Z’s buying decision process towards organic facial care products. Besides, impact of social factors, including family and reference group, on buying decision process were measured. Quantitative research consisting of 500 samples was employed via online survey by using convenience sampling method at the confidence level of 95%. The results showed that most of the respondents were female, studying in high school and earned less than 10,000 baht per month. Besides, social factors of organic facial care products buying were raised mainly through reference group factors. Additionally, buying decision process was in a high level, especially in the alternative evaluation process. From hypothesis testing, overall buying decision process was positively affected by family and reference group. Reference group factors played the important role that had the major impact on buying decision process. It was recommended that organic facial care producers or sellers should employ influencers as main contact points to drive sale revenues and building trust through testimonial of the products.